1985
DOI: 10.1159/000145979
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy of Human Submandibular Gland

Abstract: The fracture surface of human submandibular gland analyzed by scanning electron microscopy is studied here. Acini showed spherical granules of 0.7 ± 0.28 µm diameter, their most distinctive feature. Some empty, septate cavities found contiguous to serous acini were considered to be mucous acini. Striated ducts had a circular lumen, with microvilli forming prominences. Blebs, some intact and others ruptured, were interpreted as apocrine secretion. The ‘separating zone’ of the striated cells was distinguishable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…The SEM observations of the surfaces allowed the direct observation of the intracellular components, especially of the true surface of the capsular structures. The present findings are similar to those reported in monkeys by Boshell et al 26 , and in man by Espinal et al 19 Our results confirm that the striated ducts present a circular section containing polygonal cells. These data are similar to those reported by Espinal et al 19 , and by Watanabe et al 24,25 The three-dimensional architecture of the collagen fibrils revealed in the present paper represents the skeletal structure of the interface acinar cell membrane connective tissue of the salivary glands in their original localization.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The SEM observations of the surfaces allowed the direct observation of the intracellular components, especially of the true surface of the capsular structures. The present findings are similar to those reported in monkeys by Boshell et al 26 , and in man by Espinal et al 19 Our results confirm that the striated ducts present a circular section containing polygonal cells. These data are similar to those reported by Espinal et al 19 , and by Watanabe et al 24,25 The three-dimensional architecture of the collagen fibrils revealed in the present paper represents the skeletal structure of the interface acinar cell membrane connective tissue of the salivary glands in their original localization.…”
Section: Discussionsupporting
confidence: 93%
“…Since this gland has not been described until now, the histological data may illustrate clearly the acinar and ductal formations of the submandibular salivary gland of the collared peccary. Histologically, our data showed that the characteristics of the acini and of the striated ductus of the collared peccary are similar to those reported in several animals, such as reported by Cowley et al, 6 Espinal et al, 19 and Nagato et al 20 On the other hand, the morphological characteristics of the ductal structures of the submandibular gland of the collared peccary may be different when compared with other mammals, such as the Koala (Phascolarctos cinereus). 3 Our data confirm that the nuclei were located in the basal region of the cells in spherical form, similar to those found in other mammals, such as reported by Estecondo et al 1 in the armadillo (Zaedyus pichiy) and by Fossati et al 21 in rats.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the fact that micropuncture studies have clearly shown that salivary glands also have segments endowed with different transport properties (Martinez, 1987;Schneyer et al, 1972), no detailed studies have been published on the 3D microanatomy of cells of mammalian salivary glands. In fact, apart from the data mentioned in our articles on the human salivary glands ; Riva et al, 1989;Tandler and Riva, 19861, the literature so far available on these organs solely concerns the distribution and topography of myoepithelial cells (mecs) in rodents (Nagato et al, 1980) and in man (Nagai and Nagai, 1985) and some aspects of cell internal structure (Espinal et al, 1985).…”
Section: Introductionmentioning
confidence: 87%